FRI0306 Serum Anti-Müllerian Hormone Levels in SLE Patients: Influence of Disease Severity and Therapy on The Ovarian Reserve. (15th July 2016) - Di Mario, C.; Petricca, L.; Gigante, M.R.; Marino, G.; Varriano, V.; Barini, A.; Canestri, S.; Barini, A.; Tolusso, B.; Ferraccioli, G.; Gremese, E.
Abstract : Background: Systemic lupus erythematosus (SLE) predominantly affects women of reproductive age and may negatively affect their fertility due to severe organ involvement and the prolonged immunosuppressive therapy used. The Anti-Müllerian Hormone (AMH) is secreted from granulosa ovary cells and serum levels of Anti-Müllerian Hormone are used as a measure of ovarian reserve, reflecting the number of primary follicles. Systemic lupus erythematosus (SLE) predominantly affects women of reproductive age and may negatively affect their fertility due to severe organ involvement and the prolonged immunosuppressive therapy used. The Anti-Müllerian Hormone (AMH) is secreted from granulosa ovary cells and serum levels of Anti-Müllerian Hormone are used as a measure of ovarian reserve, reflecting the number of primary follicles. Objectives: To compare serum levels of AMH in a cohort of patients with SLE and healthy controls and to assess whether the presence of the disease, the treatments used and/or other clinical parameters may affect the ovarian reserve. Methods: Eighty-six consecutive female patients with SLE of childbearing age, aged between 18 and 42 years and with regular menses and 44 healthy controls age-matched were evaluated. Anti-Müllerian Hormone levels were measured in peripheral blood samples (kit AMH Gen II ELISA, Beckman Coulter). Clinical and demographic characteristics, disease duration, pattern of organ involvement and previous and current therapies were collected at the time of sampling. Fourteen patients (16.3%) had been treated with cyclophosphamide (CTX, cumulative dose 8.3 ± 5.4 g), and of the remaining, 39 (45.3%) with other DMARDs (methotrexate-MTX, azathioprine, mycophenolate mofetil, cyclosporine) and 33 (38.4%) with anti-malarials only. Results: Patients with SLE had a mean age of 30.4±6.3 years, a disease duration of 7.7±5.1 years and 25 patients (33.3%) had a severe organ involvement (mainly renal and neurological, 14 were treated with cyclophosphamide, 11 with other DMARDs). Serum levels of AMH were comparable between patients and controls (4.2±3.3 vs 5.0±3.1 ng/ml, respectively, p=0.2). Considering patients on the basis of organ involvement, patients with major organ involvement had AMH levels (3.6±2.8 ng/ml) significantly lower than control subjects (p=0.03); no difference was found between patients with minor organ involvement (AMH 4.4±3.4 ng/ml) and control subjects (p=0.4). Considering the treatments used, patients with major organ involvement treated with cyclophosphamide showed serum AMH levels lower than controls (2.9±3.3 ng/ml, p=0.04). Moreover, patients previously exposed both to CTX and MTX, showed the lower AMH levels with respect to other groups (1.1±1.9 ng/ml, p=0.01). There were no associations between the use of other DMARDs than cyclophosphamide and lower AMH levels in SLE patients compared to controls. Conclusions: In the whole cohort of SLE patients, the ovarian reserve was overall comparable to that of healthy controls, whereas a reduction of the ovarian reserve was associated with the use of cyclophosphamide and the severity of the disease. Disclosure of Interest: None declared